Carbon dioxide capture and functionalization by bis(N-heterocyclic carbene)-borylene complexes - Fan, Jun; Koh, An-Ping; Wu, Chi-Shiun; Su, Ming-Der; So, Cheuk-Wai (Nature communications, 2024)
Derivatives of free monocoordinated borylenes have attracted considerable interest due to their ability to exhibit transition-metal-like reactivity, in particular small molecules capture. However, such complexes are rare as the formation is either endergonic, or the resulting adduct is a transient intermediate that is prone to reaction. Here, we present the synthesis of two bis( N -heterocyclic carbene)-borylene complexes capable of capturing and functionalizing carbon dioxide. The capture and subsequent functionalization of CO 2 by the bis(NHC)-disilylamidoborylene 1 is demonstrated by the formation of the bis(NHC)-isocyanatoborylene-carbon dioxide complex 3 . Reversible capture of CO 2 is observed using the bis(NHC)-mesitylborylene 2 , and the persistent bis(NHC)-mesitylborylene-carbon dioxide adduct 4 can be stabilized by hydrogen bonding with boric acid. The reactions of 4 with ammonia-borane and aniline demonstrate that the captured CO 2 can be further functionalized. Bis( N -heterocyclic carbene)-borylene complexes are capable of capturing and functionalizing CO 2 , but stable single-site-boron-carbon dioxide adducts are rarely reported. Here, the authors report the synthesis of a stable borylene-CO 2 complex as well as the functionalization of the captured CO 2 .